Cutaneous melanoma - guidelines for diagnostics and therapy in 2016 - Piotr Rutkowski; Piotr J. Wysocki; Anna Nasierowska-Guttmejer; Jacek Fijuth; Ewa Kalinka-Warzocha; Tomasz Świtaj; Arkadiusz Jeziorski; Milena Szacht; Wojciech Zegarski; Wojciech M. Wysocki; Lidia Rudnicka; Witold Owczarek; et al. (Termedia Publishing House, 2016)
Dermoscopy is currently the standard method for clinical differential diagnosis of cutaneous melanoma and for qualifying a lesion for excisional biopsy. Full thickness excisional biopsy of suspicious melanomatous skin lesions likely to be diagnosed as early melanomas is crucial in establishing the diagnosis and defining prognostic factors. Early diagnosis and surgical removal of cutaneous melanoma not only improves patients' prognosis but is also associated with approximately 90% likelihood of cure. The next steps in the therapeutic management of cutaneous melanoma following excisional biopsy are radical scar excision with adequate margins and sentinel lymph node biopsy. Radical lymph node dissection is recommended in the case of regional lymph node metastases. High-risk patients (lymph node involvement and/or ulcerated primary lesion) should be advised to participate in prospective clinical trials on adjuvant therapy. Melanoma patients with distant metastases are still characterized by poor outcomes. In patients with metastatic disease testing for the presence of BRAF gene mutation is mandatory. Patients with metastatic disease should be considered for participation in clinical trials. Long-term survival is confined to a selected group of patients undergoing resection of isolated metastatic lesions. In systemic - mainly first-line - therapy of patients with BRAF V600 mutation the BRAF inhibitor vemurafenib or dabrafenib (preferentially in combination with a MEK inhibitor) may be employed and independently of mutational status immunotherapy with anti-PD-1 antibodies (nivolumab or pembrolizumab) and eventually ipilimumab (anti-CTLA4 antibody) may be used.